John Mullan : The Tumultuous Life of a Western Road Builder - Petersen, Keith (Book collections on Project MUSE., 2014)
"John Mullan's celebrated road--a 625-mile link that connected the Missouri and Columbia Rivers--established the West Point graduate as an accomplished engineer ... Keith Petersen takes a fresh look at Mullan, whose road significantly impacted the development of the Northwest. His story includes business partnerships and personal relationships with some of the West's most intriguing characters: Father Pierre-Jean DeSmet, General William T. Sherman, Chico founder John Bidwell, Idaho gold discoverer Elias Pierce, Yakama Indian chief Owhi, and others."--Publishers website.